Valdosta High School Scrapbook 3, August – November 1961 - Lowndes County Highschool (My University, 1961)
Sports Scrapbooks regarding the Lowndes County Highschool Football team during the 1961 Football Season. This item primarily contains newspaper cutouts and pictures
Item includes 1 PDF file with 91 pages and a title page
Keywords: Lowndes County (Ga.); Scrapbooks; Newspapers